CASE REPORT Mixed cryoglobulinemia type II – benefitial result of therapy - Czubek, Maria; Czuszyńska, Zenobia; Szczerkowska-Dobosz, Aneta; Siedlewicz, Aleksandra; Jasiel-Walikowska, Elżbieta (Reumatologia/Rheumatology, 2005)
Cryoglobulinemia is a systemic syndrome characterised by vasculitis and presence of circulating serum immunological complexes which are cold-precipitable (cryoglobulins). There are three types of cryoglobulinemias. Type I is composed of single, monoclonal immunoglobulins, types II and III are composed of immunocomplexes formed by monoclonal (in type II) or polyclonal (in type III) IgM with rheumatoid factor activity. Cryoglobulinemia could be an idiopathic or secondary disorder. The known causes of secondary cryoglobulinemia include infections, autoimmune diseases and limfoproliferative disorders. There is unknown one efficient method of treatment of cryoglobulinemia. The aim of this study was to present good result of treatment of idiopathic cryoglobulinemia typ II with metylprednisolon and cyclophosphamid.